Cardamonin induces G2/M phase arrest and apoptosis through inhibition of NF-κB and mTOR pathways in ovarian cancer - Ruibin, Jiang (Aging (Albany NY), 2020)
Cardamonin, a natural chalcone, is reported to induce apoptosis and inhibit cancer cell growth. However, the mechanisms underlying the therapeutic effects of cardamonin remain to be established. Here, we have focused on cardamonin-induced apoptosis in ovarian cancer cells, both in vitro and in vivo. The effects of cardamonin on cell cycle patterns and apoptotic responses of cells were assessed in this study. Western blot was employed to determine the effects of cardamonin on expression of cell cycle- and apoptosis-related proteins. Our results indicate that cardamonin suppresses cancer cell growth by inducing G2/M phase arrest and apoptosis through targeted inhibition of NF-κB and mTOR pathways. The collective findings provide novel insights into the pathways responsible for the anticancer effects of cardamonin and support its potential utility as a clinical therapeutic agent for ovarian cancer.